INVESTIGATING THE IMPACT PROPERTIES OF COMPOSITES REINFORCED WITH WOVEN FABRICS - Yalcin, Enver B.; Marsoglu, Muzeyyen; Gunay, Volkan (YILDIZ TECHNICAL UNIV, 2013)
In this study, composites were produced by cold press moulding method, using 0 degrees/degrees 0. oriented woven glass and polyester matrix material. Impact tests were applied to composites in several impact energy levels (100J, 250J, 350J, 500J, 750J) by using Instron Dynatup 9250HV high velocity impact test machine. After impact tests, damages on the composites were examined by graphs which were achieved from the software of the impact test machine. Main objective of this work was to determine the energy absorbtion of the composite materials during impact tests. Results shall be used to enhance the composite production process and correspondingly achieve to enhance the impact resistance of the material.
Keywords: Impact test; woven; polyester; Engineering